Application Of Educational Learning Islamic Religion In Formation Islamic Personal Character - Rabbani, Fauziah Risa; Yusri, Nadia; Putra, Rizky Giansyah (-, 2024)
There are several factors that influence students' interest in learning, this can come from family factors, especially parents and can also come from environmental factors in the learning class depending on how the teacher provides knowledge so that it can increase students' interest in learning, one of which is the appropriate learning method. used by a teacher. Teachers must be clever in using learning methods because if a teacher uses this learning method incorrectly it will have a very negative impact on students' interest in learning and learning outcomes. The lecture method is one of the traditional teaching methods that has been used for the longest time in the teaching and learning process from elementary to tertiary level considering its very practical and efficient nature for a teaching model with a very large number of students and material. The aim of this research is to find out whether the lecture method can influence elementary school students' interest in learning.